Role of Big data Capabilities and Adoption in Innovation: Moderating Influence of Employee Engagement - Shafaat Tahir (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: South Korea’s commitment to fostering a digitally well-informed society and its early embrace of mobile technologies has positioned the country at the forefront of the global mobile tech arena. South Korea has emerged as a global power house in the technology sector, with its mobile tech industry playing a pivotal role in the country’s economic landscape. Korean mobile tech companies have garnered international recognition for their innovation, cutting-edge technologies, and influential contributions to the global tech ecosystem. This descriptive and quantitative study aims to investigate the intricate relationships among key variables, namely big data adoption, big data analytics capabilities, employee engagement, digital innovation, and innovative behavior within the framework of Korean mobile tech companies. Methodology: Utilizing a cross-sectional design and convenience sampling, data was collected from 213 managers working in Korean mobile tech industry. The research draws on the Resource-Based View (RBV) and Dynamic Capability Theory to provide a comprehensive understanding of the interplay between these factors. The study employs Smart PLS (Partial Least Squares) for analysis, leveraging its suitability for complex structural equation modeling. Findings: The research aims revealed the nuanced significant associations between big data dynamics, employee engagement, and innovation within the unique context of Korean mobile tech companies. Implications/Novel Contribution: The findings are anticipated to contribute valuable insights to both academia and industry by offering a robust examination of the mechanisms shaping innovation in Korean mobile tech companies. As organizations navigate the evolving landscape of technology and data-driven decision-making, the outcomes of this study aim to inform strategic decision-making and enhance the understanding of the factors influencing digital innovation and innovative behavior in this specific sector. The study brings policy insights for tech sector overall and for Korean Mobile sector in specific.